La Potencia del Oxímoron en la Epistemología de las Ciencias Humanas - Dalmau, Iván (2014)
The aim of is this work is to discuss about the uses of oxymoron in the epistemology of human sciences. Because of that, we will focus on the conceptualizations of Michel Foucault and Alfred Schutz, especially we will intend to analyze the potentiality of the foucaultean notion of “historical a priori” and the schutzian conceptualization of the language as a “socio historical a priori component” of the social life. By this way, we will intend to show how this two philosophers made contributions beyond the dichotomy between “subjectivism” and “objectivism”.